OPTIMIZATION OF GUMITIR FLOWER EXTRACT (TAGETES ERECTA L.) SUNSCREEN CREAM: SIMPLEX LATTICE DESIGN METHOD - I Gusti Ngurah Agung Windra Wartana Putra; I Gusti Ayu Agung Septiari (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2023)
Background: Sunscreen cream is used to protect the skin from the bad effects of sunlight. Making a good sunscreen cream requires paying attention to the composition of the constituent compounds to obtain a standardized cream form quality. Formula optimization is carried out in each cream formulation, including to produce of Gumitir flower extract sunscreen cream. Objective: The aim of this research is to produce an optimum formula for Gumitir flower extract sunscreen cream. Methods: The method used in this research is the Simplex Lattice Design optimization method to find the optimum base between stearate acid cream base and triethanolamine. Results: Optimization results show that variations in stearic acid and triethanolamine cream bases influence the physical properties of viscosity and adhesiveness of sunscreen cream preparations, with stearic acid as the dominant factor influencing viscosity. Conclusion: The conclusion obtained from this research is that the optimum formula for Gumitir flower extract sunscreen cream was obtained with a base composition of 13.5% stearic acid and 2.5% triethanolamine. Keywords: Optimization; Gumitir; Extract; Sunscreen